First measurement of the 33 Cl( p , α ) 30 S reaction - Deibel, C. M.; Rehm, K. E.; Figueira, Juan Manuel; Greene, J. P.; Jiang, C. L.; Kay, B. P.; Lee, H. Y.; Lighthall, J. C.; Marley, S. T.; Pardo, R. C.; Patel, N.; Paul, M.; et al. (American Physical Society, 2011)
Fil: Deibel, C. M.. Michigan State University; Estados Unidos. Argonne National Laboratory; Estados Unidos